Polymer-Stabilized Elemental Boron Nanoparticles for Boron Neutron Capture Therapy: Initial Irradiation Experiments - Bekarevich, Raman (My University, 2022)
Sufficient boron-10 isotope (10B) accumulation by tumor cells is one of the main requirements for successful boron neutron capture therapy (BNCT). The inability of the clinically registered 10B-containing borophenylalanine (BPA) to maintain a high boron tumor concentration during neutron irradiation after a single injection has been partially solved by its continuous infusion; however, its lack of persistence has driven the development of new compounds that overcome the imperfections of BPA. We propose using elemental boron nanoparticles (eBNPs) synthesized by cascade ultrasonic dispersion and destruction of elemental boron microparticles and stabilized with hydroxyethylcellulose (HEC) as a core component of a novel boron drug for BNCT. These HEC particles are stable in aqueous media and show no apparent influence on U251, U87, and T98G human glioma cell proliferation without neutron beam irradiation. In BNCT experiments, cells incubated with eBNPs or BPA at an equivalent concentration of 40 µg 10B/mL for 24 h or control cells without boron were irradiated at an accelerator-based neutron source with a total fluence of thermal and epithermal neutrons of 2.685, 5.370, or 8.055 × 1012/cm2. The eBNPs significantly reduced colony-forming capacity in all studied cells during BNCT compared to BPA, verified by cell-survival curves fit to the linear-quadratic model and calculated radiobiological parameters, though the effect of both compounds differed depending on the cell line. The results of our study warrant further tumor targeting-oriented modifications of synthesized nanoparticles and subsequent in vivo BNCT experiments.
PUBLISHED
Keywords: Polymer stabilization; Hydroxyethylcellulose; Elemental boron nanoparticles; Boron neutron capture therapy; Accelerator-based neutron source; Cancer; Nanoscience & Materials; BORON; Boron Neutron Capture Therapy